The Effect of Knowledge About Healthy Homes on The Incidence of TB in The Work Area of Aisandam Community Health Center, Teluk Wondama District - Momot, Simon Lukas; Djamanmona, Rolyn Frisca (YCAB Publisher, 2025)
Background: Tuberculosis (TB) remains a critical public health challenge, especially in areas like the Aisandam Health Center Work Area, Teluk Wondama Regency, Southwest Papua, Indonesia. Environmental and socio-economic factors are crucial in TB transmission. Promoting knowledge about healthy homes is essential to reducing disease risk, yet the relationship between community knowledge of healthy homes and TB incidence requires further investigation. This study aims to assess community knowledge about healthy homes and its influence on TB incidence. Objective: The study aims to evaluate the level of knowledge regarding healthy homes in the community and analyze its impact on the incidence of TB. Method: Using an observational analytical approach with a case-control design, the study examines the link between knowledge of healthy homes and TB incidence, identifying current cases of TB and past risk factors. Result: Key respondent characteristics included age, gender, education, marital status, occupation, income, religion, ethnicity, and TB treatment duration. Most respondents were aged 19-44 years (62.5%) with basic education (56.3%). The majority were married (87.5%), housewives or unemployed (62.5%), and earned less than 1 million IDR monthly (93.8%). Statistical analysis revealed no significant relationship between knowledge about healthy homes and TB incidence (p = 0.790). The odds ratio was 0.750, with a 95% confidence interval between 0.0903 and 6.23. Conclusion: The study found no significant relationship between knowledge about healthy homes and TB incidence in the Aisandam Health Center Work Area, suggesting that other factors may be more influential. Keywords: tuberculosis; marital status; occupations; economic factors; Indonesia